Investigation of potential solar induced ventilation strategy in hot and humid climate - Mohammad Yusoff, Wardah Fatimah; Salleh, Elias; Adam, Nor Mariah; Sapian, Abdul Razak; Hamzah, Zabidi (Faculty of Design & Architecture, Universiti Putra Malaysia, 2012)
The use of solar energy in solar induced ventilation helps to enhance thestack ventilation, which is normally less efficient in hot humid climate due to the small temperature difference between the inside and outside of naturally ventilated buildings. This paper aims to examine a potential solar induced ventilation strategy for hot humid climate. There are two methods used, which are a literature survey and a preliminary test. The literature survey was executed on the Trombe wall, solar chimney and roof solar collector. This survey resulted in the combined roof solar collector and vertical stack as the most appropriate strategy. A preliminary test using a physical model was executed in the actual environmental conditions. The findings indicate that the proposed strategy attained the air temperature difference (Ti-To) of 8.5ºC for 633 W/m² solar radiation. This air temperature difference was more than the usual air temperature difference between the inside and outside of naturally ventilated buildings in Malaysia. Hence, the paper concludes that the proposed strategy is able to enhance the stack ventilation effect in hot and humid climate